Undergraduates’ views of assessment in higher education: a study carried out in Portugal - Santos, Patricia (2017)
This paper looks at how undergraduates look at assessment in Higher Education. It focuses on their views about assessment practices in five Portuguese public universities. The main purpose is to look at the students’ perceptions of assessment in higher education taking into account the assessment methods used, the influence of assessment in their motivation to learn as well as self-regulation of the learning process. Data were collected through questionnaires in five Portuguese Public Universities in different fields of knowledge. An intervention project focused on Assessment for Learning (AfL), with students enrolled at an Engineering programme, in one public university in Portugal, in one course with student-centred methodologies and AfL practices was also carried out and evaluated. Preliminary findings are presented according the categories emerging from the data. Issues of assessment methods, the connection between teaching, learning and assessment as well as the impact of AfL environments on students’ perceptions are analysed. Implications of the findings for assessment, teaching and learning process are discussed.